Breaking through : communicating to open minds, move hearts, and change the world - Susman, Sally (Ascent Audio, 2023)
A global pandemic. A roller-coaster economy. Political tensions ready to ignite, and common civility at an all-time low. For leaders, the pressures and the stakes could not be higher. And in such a stormy, often dangerous world, communications can no longer be considered a soft skill. The ability to lead and drive the public conversation is a rock-hard competency. In this wise and inspiring book, Sally Susman, the renowned head of corporate affairs at global biopharmaceutical giant Pfizer, tells the fascinating story of how the multinational managed the massive communications challenge that came with Covid and the race to produce an effective vaccine. Just as crucial as creating the vaccine itself was the task of winning people's hearts and minds, and Susman highlights the principles that enabled her to break through, connect, and help move people forward, not only at Pfizer but over a stellar career. She shows how clarifying and channeling your intention is an essential first step: What are you trying to say? She illustrates how, in order to be effective, leaders need to muster the courage for candor; and how, in order to connect, they must both disarm with humility and delight with humor. As a gay, married woman, she talks forthrightly about the challenges and opportunities of embracing who you are, both at home and in the workplace.